PERINTISAN DAN PENGEMBANGAN KELAS BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) DI TINGKAT PERGURUAN TINGGI DI INGGRIS: PELUANG DAN TANTANGAN - Leni Amelia Suek (Jurnal Lazuardi, 2020)
ABSTRACT This research is a descriptive study that analyzes the opportunities and challenges in pioneering and developing an Indonesian language class for foreign learners (BIPA) at the University of Nottingham in England. This study is based on the experience of the author who is also the pioneer of the BIPA program at the University of Nottingham which is supported by literature studies. Opportunities of BIPA program in overseas are the internationalization of Indonesian in the world, strengthening diplomatic relations between the two countries, promoting and widening cooperation between various universities in Indonesia and abroad both in academics and scholarships affairs, enlarging the community of Indonesian language and culture overseas, business for universities in Indonesia and other language institutions, and increasing the number of tourists in Indonesia. The challenges are related to curriculum development, quality of teaching, teaching methods and management of BIPA program at the University of Nottingham in United Kingdom. This BIPA program ran succesfully despite the challenges because the opportunities have been realized. Keywords: BIPA, Opportunities, Challenges, Pilot Program